A low-speed centrifugation concept leads to cell accumulation and vascularization of solid platelet-rich fibrin: an experimental study in vivo. (3rd April 2019) - Kubesch, Alica; Barbeck, Mike; Al-Maawi, Sarah; Orlowska, Anna; Booms, Patrick F.; Sader, Robert A.; Miron, Richard J.; Kirkpatrick, Charles.J.; Choukroun, Joseph; Ghanaati, Shahram
Abstract: Platelet-rich fibrin (PRF) is generated from the patients' own venous blood by a single centrifugation step without the additional use of anticoagulants. Based on the previously described LSCC (low-speed centrifugation concept), our group showed that modification of the centrifugation setting, that is, reducing the relative centrifugal force (RCF) and mildly increasing the centrifugation time, resulted in modified solid and liquid PRF-matrices with increased number of platelets, leukocytes, and growth factors' concentrations. The aim of this study was to determine whether RCF reduction might also result in different tissue reactions toward the two PRF-based matrices, especially vascularization and cell distribution in vivo . Two centrifugation protocols (PRF-high [719 g] and PRF-medium [222 g]) were compared in a subcutaneous implantation model of SCID mice at 5 and 10 days. Histological and histomorphometrical analyses were performed to quantify lymphocyte, neutrophil, human macrophage, and monocyte populations. CD31 was used to detect newly formed vessels, while all human cells were detected by using human vimentin as a pan-cellular marker. The results demonstrated that PRF-high elicited a dense and stable fibrin structure and prevented cellular penetration of the host tissue. By contrast, PRF-medium was more porous, had a significantly higher in vivo vascularization rate, and included significantly more human cells, especially at day 10, compared to PRF-high. These findings highlight the possibility of modifying the structure and composition of PRF matrices and thus selectively altering their regenerative potential in vivo . Clinical studies now must evaluate the different PRF matrices for bone and soft-tissue regeneration to validate possible benefits using personalized preparation protocols.